Periodontal indexes of two types of 3 x 3 retainers: 0.032-in SS V-loop versus 0.0215-in SS coaxial - a randomized crossover trial - Diogo Marques SAPATA; Cléverson de OLIVEIRA E SILVA; Renata Corrêa PASCOTTO; Thais Maria Freire Fernandes POLETI; Maristela Sayuri Inoue ARAI; Adilson Luiz RAMOS (Dental Press Editora, 2024)
ABSTRACT Objective: This randomized crossover trial evaluated periodontal indexes of two types of 3 x 3 retainers (a modified 0.032-in SS V-loop retainer and a conventional 0.0215-in SS coaxial wire retainer) after bonded for six months. Also, bonded failure rate, and a questionnaire about comfort, ease of cleaning and overall preference were recorded. Material and Methods: 15 patients were enrolled in this study who used both retainers for six months each, having a 15-day wash-out interval between each bonded retainer usage. The following periodontal index were recorded: Plaque Index (PI), Calculus Index (CI) and Gingival Index (GI). Patients answered a questionnaire to assess comfort, ease of cleaning and overall retainer-type preference. Rate of bonding failure was also evaluated. Results: V-Loop retainer showed higher PI (P<0.05) as compared to conventional 0.0215-in coaxial wire retainer. However, CI and GI presented no statistically significant differences between both types of retainers. The conventional 0.0215-in coaxial wire retainer was chosen as the most comfortable (p<0.05), although no statistically significant differences were found for all other questionnaire answers. Bonding failure events were more observed in the 3x3 V-Loop retainer (p<0.002), as compared to the conventional 0.0215-in coaxial retainer. Conclusion: V-Loop retainer showed higher PI (p<0.05), higher bonding failure rate and less comfortable, as compared to conventional 0.0215-in coaxial wire.